Cross-sections in photonuclear reactions with multiple neutron emission - Bezshyyko, O.A.; Vodin, O.M; Golinka-Bezshyyko, L.O.; Kotenko, A.V.; Kushnir, V.A.; Lubynets, O.V.; Mitrochenko, V.V.; Olejnik, S.M.; Perezhogin, S.A.; Vallerand, C. (Вопросы атомной науки и техники, 2019)
The energy dependence of the reaction cross-sections A(γ,xn)(A-xn) was studied in the energy range 19...70 MeV, i.e. beyond Great Dipole Resonance (GDR) region. Experimental data were taken from international database EXFOR for range of nuclear mases (55 < A < 209). Theoretical values of cross sections were obtained using TALYS-1.8 code. Several models of level densities with both enabled and disabled pre-equilibrium mechanism were considered in our simulations. Obtained results let us to make conclusions about different mechanisms of photonuclear reactions on certain nuclei, energy dependence of their relative contribution. Метою роботи є вивчення залежності поперечних перерізів у реакції А(γ,xn)(A-xn) від енергії гамма-квантів у діапазоні 19...70 МеВ, тобто за межами області великого дипольного резонансу. Експериментальні дані були взяті з міжнародної бази даних EXFOR для широкого спектра ядерних мас (55 < A <209). Теоретичні значення поперечних перерізів отримані з використанням коду TALYS-1.8. У наших симуляцiях були розглянуті кілька моделей щільності рівнів з урахуванням передрiвноважних механізмів. Отримані результати дозволяють зробити висновки про різні механізми фотоядерних реакцій на деяких ядрах i про їх відносний внесок у залежності від енергії γ-квантів. Целью работы является изучение зависимости поперечных сечений в реакциях A(γ,xn)(A-xn) от энергии гаммаквантов в диапазоне 19...70 МэВ, т. е. за пределами области большого дипольного резонанса. Экспериментальные данные были взяты из Международной базы данных EXFOR для широкого спектра ядерных масс (55 < A < 209). Теоретические значения поперечных сечений получены с использованием кода TALYS-1.8. В наших симуляциях были рассмотрены несколько моделей плотности уровней с учетом предравновесных механизмов. Полученные результаты позволяют сделать выводы о различных механизмах фотоядерных реакций на некоторых ядрах и об их относительном вкладе в зависимости от энергии γ-квантов.